Penerapan Model Pembelajaran Auditory Intellectually Repetition (AIR) Berbantuan Aplikasi Microsoft Math Solver untuk Meningkatkan Kemampuan Pemahaman Konsep Matematis Siswa SMP - Harahap, Mardiah Hannum; Juariah; Rachmawati, Tika Karlina; Wiyanto, Yuli Tri (Jurnal Analisa, 2025)
This research aims to improve the ability to understand mathematical concepts of junior high school students through the application of the Auditory Intellectually Repetition (AIR) learning model assisted by the Microsoft Math Solver application. This study uses a quantitative approach with the quasi experiment method. The population in this study consisted of four classes with a sample of two classes selected through cluster random sampling techniques, namely class VII-A as the control class and class VII-B as the experimental class. The results of the study show that the implementation of teacher and student activities in the learning process of Auditory Intellectually Repetition (AIR) assisted by the Microsoft Math Solver application is categorized as very good. In addition, the improvement of students' ability to understand mathematical concepts using the Auditory Intellectually Repetition (AIR) learning model assisted by the Microsoft Math Solver application is better than the conventional learning model, and students' attitudes towards the application of the Auditory Intellectually Repetition (AIR) learning model assisted by the Microsoft Math Solver application were categorized as positive.